Navigating הבל (hbl): Qohelet's Meaning of Life and its Affinity with Frankl's Logotherapy - Christian Nito Antasuda Sanchez; Bernadus Dirgaprimawan (Fakultas Teologi, Universitas Sanata Dharma, 2024)
How can Qohelet in the book of Ecclesiastes give us a new perspective on the modern understanding of the meaning of life? For us to answer this question, the paper attempts to investigate the concept of the word commonly translated as ‘absurd,’ ‘worthless,’ or ‘meaningless’ used by Qohelet, originally a Hebrew word הבל (hbl). In order to clarify Qohelet's perspective of life’s meaning, the paper uses a word study on הבל (hbl). The paper aims to discuss that הבל (hbl) can properly be read as a symbolic metaphor which is ‘vapor’ that can have varying degrees of meaning which include insubstantiality, transience, and foulness. By understanding Qohelet's concept of הבל (hbl) as a symbolic metaphor, the paper elucidates how to better understand the perspective of the book of Ecclesiastes on the meaning of life as it squares with Viktor Frankl’s theory of logotherapy, a leading contemporary view of life’s meaning in modern existential philosophy. Finally, the paper encourages a new examination of life's intricacies and aims to provide insights that resonate with today's meaning-seekers by tying the book of Ecclesiastes to the writings of Viktor Frankl. Each of our life journeys is unique, nevertheless, the paper provides a new perspective and suggests common values for which we all can travel forward in life to seek meaning in our daily lives.